Sporicidal activity of mixtures of alcohol and hypochlorite. Issue 2 (February 1978) - Coates, D; Death, J E
Abstract : In an investigation of the activity against Bacillus subtilis spores of various mixtures of alcohol and sodium hypochlorite 50% methanol with enough hypochlorite to provide 2000 parts per million available chlorine water was the most sporicidal. This mixture, both when freshly prepared and for at least eight hours after mixing, achieved a five-log reduction in spore count in 10 minutes. The sporicidal activity of mixtures containing the same initial level of available chlorine was found to vary with the alcohol, initial alcohol concentration, and age of the mixture. Such mixtures may be useful for disinfecting heat-sensitive instruments.